Espatolino - Gómez de Avellaneda, Gertrudis, 1814-1873 (Narrativa (Linkgua Ediciones), 2019)
Espatolino is a villain who acts in Naples and Rome. Agents and spies have kept abreast of government and police movements, as well as the routes of travelers. Espatolino is agile and skillful with weapons. His name is a legend. But one day he meets a beautiful woman: Anunziata. From that moment on things changed within the gang and within Espatolino himself, who faces opposition from a new threat.